2019
DOI: 10.29091/9783954907090
|View full text |Cite
|
Sign up to set email alerts
|

The Triconch House

Abstract: Lastly, I dedicate this volume to the memories of my father, whom I owe so much, and Rebecca Molholt Vanel, whose friendship and repeated assurances that clamoring hordes were waiting for this book made its completion possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Data from Aphrodisias have been published extensively, with many new volumes appearing in the main excavation series and relating to general study and discussion. Sculpture studies and monographs concerning the city's civic buildings occupy an important place among publications: recent publications include detailed research on the Roman Sebasteion, built in 20-60 AD, considering how the monument served the needs of both the cult of Aphrodite and the imperial cult, and exploring its anastylosis; and research on the theatre, the basilica, and on the columned sarcophagi found around the city wall and various parts of the town (Smith 2013;Stinson 2016;de Chaisemartin and Theodorescu 2017;Öğüş 2018;van Voorhis 2018;Berenfeld 2019). Other publications from Aphrodisias include studies on settlement history and the regional survey results (Ratté and De Staebler 2012;Smith et al 2016;Hugh 2022).…”
Section: Cariamentioning
confidence: 99%
“…Data from Aphrodisias have been published extensively, with many new volumes appearing in the main excavation series and relating to general study and discussion. Sculpture studies and monographs concerning the city's civic buildings occupy an important place among publications: recent publications include detailed research on the Roman Sebasteion, built in 20-60 AD, considering how the monument served the needs of both the cult of Aphrodite and the imperial cult, and exploring its anastylosis; and research on the theatre, the basilica, and on the columned sarcophagi found around the city wall and various parts of the town (Smith 2013;Stinson 2016;de Chaisemartin and Theodorescu 2017;Öğüş 2018;van Voorhis 2018;Berenfeld 2019). Other publications from Aphrodisias include studies on settlement history and the regional survey results (Ratté and De Staebler 2012;Smith et al 2016;Hugh 2022).…”
Section: Cariamentioning
confidence: 99%